Higher Education and the American Dream - Marvin Lazerson (Central European University Press, 2010)
""Marvin Lazerson's new book is exactly what is needed: a readable, cogent explanation of how the U.S. can have the best system of higher education in the world, but also a system that seems to be coming apart at the seams." -Susan Fuhrman, President Teachers College, Columbia University, President of the National Academy of Education ""In prose remarkable for its clarity and analysis remarkable for its fair-mindedness, this volume delivers a penetrating, nuanced account of American universit...